SPE Middle East Oil and Gas Show and Conference 2009
DOI: 10.2118/120303-ms
|View full text |Cite
|
Sign up to set email alerts
|

Two-Zone Commingled Production using Intelligent Well Completion Coupled with ESP through a Hydraulic Disconnect Tool

Abstract: A dual-reservoir completion using Intelligent Well system together with an electrical submersible pump (ESP) in a high-rate well was recently deployed in one of the large carbonate fields in Saudi Arabia. The well was equipped with ESP to provide artificial lift to pump the oil to a centralized processing facility that is far a way from the well through a 2-zone "Smart" well completion, which remotely controls fluid inflow from each of the two laterals. This completion enables commingled production from two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Reservoir-A has excellent reservoir qualities and is laterally homogeneous in terms of petro-physical properties across the entire field. (Ansah, 2009) Collected cores along the field were utilized for fracture modeling along with dynamic flow data, pressure transient analysis and drilling information. Reservoir B is located below Reservoir-A, and is separated by a 300' impermeable carbonate mudstone formation.…”
Section: Field Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reservoir-A has excellent reservoir qualities and is laterally homogeneous in terms of petro-physical properties across the entire field. (Ansah, 2009) Collected cores along the field were utilized for fracture modeling along with dynamic flow data, pressure transient analysis and drilling information. Reservoir B is located below Reservoir-A, and is separated by a 300' impermeable carbonate mudstone formation.…”
Section: Field Characterizationmentioning
confidence: 99%
“…Crude oil fingerprint tests were also conducted and results showed that both reservoirs shared the same fluid properties (Ansah, 2009). Crude oil fingerprint tests were also conducted and results showed that both reservoirs shared the same fluid properties (Ansah, 2009).…”
Section: Historic Datamentioning
confidence: 99%
“…The need to control fluid production from each reservoir was critical, especially in the areas of proven inter-reservoir communication. 3 Recall that fractures have been identified in both reservoirs and are suspected to be conduits for the communication between the reservoirs. It is only the application of smart wells equipped with ICVs (Figure 4), that will provide the capability to control and optimize fluid production, from separate laterals in the separate reservoirs, without a major workover operation,.…”
Section: Field Development and I-fieldmentioning
confidence: 99%
“…3 Recall that fractures have been identified in both reservoirs and are suspected to be conduits for the communication between the reservoirs. This multiple-pay environment called for commingling production from these reservoirs, to reduce development costs and optimize field development.…”
Section: Field Development and I-fieldmentioning
confidence: 99%